Tea-Table Talk - Jerome, Jerome K. (Jerome Klapka), 1859-1927 (Salt Lake City, UT : Project Gutenberg, 2000)
"Tea-Table Talk" by Jerome K. Jerome is a collection of humorous essays and dialogues penned in the late 19th century. The text delves into conversations among a diverse group of characters who discuss various societal themes, personal experiences, and observations about love, relationships, and the intricacies of human behavior. The opening of the book presents an animated discussion at a gathering, where characters such as the Woman of the World, the Minor Poet, and the Girton Girl engage in witty repartee about the nature of love letters and relationships. Each character offers their unique perspective, leading to amusing anecdotes and philosophical musings about romantic encounters and human emotions. The tone is light-hearted yet thought-provoking, setting the stage for more explorations into the complexities of love and societal norms throughout the work. (This is an automatically generated summary.)
Release date is 2000-10-01
Transcribed from the 1903 Hutchinson & Co. edition by David Price
Keywords: England -- Social life and customs -- Fiction; Conversation -- Fiction